Green synthesis of Fe2O3-MnO2 nano-hybrids on pumice for complete degradation of pharmaceutical pollutants - Abdulrazzaq Hammal; Ahmad Sulaiman (PLoS ONE, 2025)
Pharmaceutical contaminants in wastewater pose critical environmental and public health risks due to their persistent nature and resistance to conventional treatment. To address this challenge, we developed an innovative, green-synthesized Fe2O3-MnO2 nano-hybrid catalyst supported on acid-activated Syrian pumice. The catalyst was prepared via an eco-friendly hydrothermal method using Laurus nobilis leaf extract as a bio-reducing agent, emphasizing sustainability. Structural characterization revealed significant enhancement in surface properties, with the modified catalyst exhibiting a high surface area (214.7 ± 3.5 m2/g) and optimized pore architecture (0.36 cm3/g volume, 6.7 nm average diameter) featuring 80% mesopores and 20% micropores. Under mild conditions (pH 7, 25°C, 0.5 g/L catalyst dose, 10 mM peroxymonosulfate), the system achieved 92.3% COD and 93.5% BOD5 removal within 3 hours for wastewater laden with the beta-lactam antibiotic amoxicillin (50 mg/L). LC-MS/MS analysis confirmed the complete degradation of the target pollutants, with no toxic intermediate byproducts detected. The catalyst exhibited exceptional stability, retaining >86% efficiency after five reuse cycles, with minimal metal leaching (Fe/Mn < 0.3 mg/L, within WHO limits). In continuous-flow mode, it maintained 89.6% COD and 90.4% BOD5 removal, demonstrating scalability. This study bridges nanotechnology and circular economy principles by valorizing locally abundant volcanic pumice (a natural waste) through an eco-friendly synthesis route, presenting a scalable and industrially viable solution for pharmaceutical wastewater treatment.